(untitled) (Eurasian Scientific Herald, 2022)
In this article it is written about institutional leaders in vocational education and training (VET) refer to those who are appointed or employed in a recognised leadership position to oversee VET programmes and institutions and who have responsibility for the goals set by the organisation that offers VET programmes.